2022
DOI: 10.5114/biolsport.2021.102930
|View full text |Cite
|
Sign up to set email alerts
|

Higher evening metabolic responses contribute to diurnal variation of self-paced cycling performance

Abstract: This study examined the effect of time of day (TOD) on physical performance, and physiological and perceptual responses to a 10-km cycling time trial (TT 10km ). Twelve physically trained subjects (20.3 ± 1.2 years, 74.3 ± 7.4 kg, 179.7 ± 5.5 cm) completed, in a randomized order, a TT 10km in the morning and in the evening. Intra-aural temperature (IAT) was measured at rest and following the TT 10km . Completion time, power output (PO), ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Moreover, such exercise regimens, encompassing multiple energy systems, movement patterns, and athletic range also have support under an evolutionary lens ( Longman et al, 2020 ). Yet, recent research examining ETOD has focused on just one mode or a combination of resistance and endurance (aerobic) exercise regimens ( Küüsmaa-Schildt et al, 2017 ; Blazer et al, 2021 ; Creasy et al, 2022 ; Souissi et al, 2022 ). Therefore, the current body of ETOD literature lacks critical data on the typical manner in which most athletes and fitness enthusiasts engage in physical activity programs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such exercise regimens, encompassing multiple energy systems, movement patterns, and athletic range also have support under an evolutionary lens ( Longman et al, 2020 ). Yet, recent research examining ETOD has focused on just one mode or a combination of resistance and endurance (aerobic) exercise regimens ( Küüsmaa-Schildt et al, 2017 ; Blazer et al, 2021 ; Creasy et al, 2022 ; Souissi et al, 2022 ). Therefore, the current body of ETOD literature lacks critical data on the typical manner in which most athletes and fitness enthusiasts engage in physical activity programs.…”
Section: Introductionmentioning
confidence: 99%
“…Souissi et al . [ 23 ] involved 12 young, normal BMI and physically trained individuals in self-paced endurance cycling and reported that the RER was insignificantly lower during the evening (17:00–18:00) than in the morning (7:00–8:00). The timing of the meal and the gender of the subjects were not specified.…”
Section: Discussionmentioning
confidence: 99%
“…Souissi et al . [ 23 ] reported that the evening session caused significantly higher oxygen consumption than the morning exercise session. Ezagouri et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, we hypothesized that ( i ) endurance running performance during the 3.000-m run and the treadmill test would be higher in the evening than in the morning [ 7 , 12 , 14 , 15 ] and ( ii ) that both blood lactate levels and HR during the incremental treadmill test would be different between the morning and evening [ 4 , 16 21 ].…”
Section: Introductionmentioning
confidence: 99%